The relevance of internal governance mechanisms to financial reports timeliness / Rahimah Mohamed Yunos. - Mohamed Yunos, Rahimah (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
The objective of the study is to identify the influence of firms' internal governance mechanisms on the timeliness of management report and auditor report. The governance examined in this study isboard independence, board size, CEO duality, audit committee meeting and audit committee expertise. Data was collected from 264 annual reports of listed companies on Bursa Malaysia for a sample period of 2013 and 2014. The results show that proportion of independent directors on board, CEO duality and frequent audit committee meeting had significant effect on the timeliness of the reports.  The findings indicate that firms' governance mechanisms influence how fast they are able to release information to the users; hence promote effective communication and maintain their accountability to its stakeholders.The result of this study is beneficial to the policymaker, management of the company and the stakeholders.